Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) XX: New descriptions from Guangxi and Guizhou - Pang, Siyu; Zhang, Qianwen; Bian, Xun (Zootaxa, 2023)
Based recent collections, we describe Eugryllacris longiproceris sp. nov. (Chinese name: 长突真蟋螽), Homogryllacris guizhouensis sp. nov. (Chinese name: 贵州同蟋螽), Phryganogryllacris flavistria sp. nov. (Chinese name: 黄纹杆蟋螽) and the female of Eugryllacris nigriabdominis Bin & Bian, 2021. Among these, Homogryllacris guizhouensis sp. nov. (Chinese name: 贵州同蟋螽) is the first described micropterous species from Guizhou Province. All the specimens are deposited in Guangxi Normal University.